Field Evaluation of the New Rapid NG-Test® SARS-CoV-2 Ag for Diagnosis of COVID-19 in the Emergency Department of an Academic Referral Hospital - Avgoulea, Kalliopi; Beredaki, Maria-Ioanna; Vourli, Sophia; Siopi, Maria; Siafakas, Nikolaos; Pournaras, Spyros (Frontiers in Public Health, 2022)
Background As the COVID-19 pandemic resurges affecting large numbers of patients, rapid, and accurate diagnosis using point-of-care tests is very important. Objectives To evaluate the NG-Test® SARS-CoV-2 Ag (NG-Test) immunoassay for qualitative detection of SARS-CoV-2 antigen in nasopharyngeal (NP) and oropharyngeal (OP) samples compared with RT-PCR, in patients attending the Emergencies of an academic referral hospital. Methods All adult ambulatory patients presenting to the Emergencies of “Attikon” University hospital (Athens, Greece) within three consecutive hours per day between December 2020 and March 2021 and for whom SARS-CoV-2 PCR testing was requested were included. Two NP and one OP samples obtained from each participant were analyzed to determine the diagnostic performance [sensitivity, specificity, positive/negative predictive values (PPV/NPV)] of the NG-Test (NP/OP swabs) in comparison to the reference RT-PCR (NP swab). Results Overall, 134/263 (51%) patients tested were RT-PCR positive, whereof 108 (overall sensitivity 81%, 95% CI 73–87%) were NP NG-Test positive (PPV 99%, NPV 83%) and 68 (overall sensitivity 51%, 95% CI 42–59%) were OP NG-Test positive (PPV 100%, NPV 66%). The test's specificity (95% CI) was 99% (95–100%) and 100% (96–100%) for NP and OP swabs, respectively. The assay's sensitivity (95% CI) for high viral load (Ct ≤25) was 99% (92–100%) and 71% (60–81%) for NP and OP swabs, respectively. Conclusions NG-Test using NP swabs detected almost all patients with high viral loads, showing satisfactory performance as a point-of-care test for NP samples obtained from patients with acute infection.